2007
DOI: 10.1021/tx700248y
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Products Inhibit Dopamine Catabolism Yielding Aberrant Levels of a Reactive Intermediate

Abstract: Recent work indicates that oxidative stress is a factor in Parkinson's disease (PD); however, it is unknown how this condition causes selective dopaminergic cell death. The neurotransmitter dopamine (DA) has been implicated as an endogenous neurotoxin to explain the selective neurodegeneration. DA undergoes catabolism by monoamine oxidase (MAO) to the reactive intermediate 3,4-dihydroxyphenylacetaldehyde (DOPAL), which is further oxidized to 3,4-dihydroxyphenylacetic (DOPAC) acid via mitochondrial aldehyde deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
138
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(141 citation statements)
references
References 45 publications
3
138
0
Order By: Relevance
“…Alternatively, DA may undergo monoamine oxidase-catalyzed oxidative deamination to produce DOPAL, which can be further metabolized by aldehyde dehydrogenase to DOPAC (16,40). Previously, we showed that lipid peroxidation, which is closely associated with oxidative stress, can inhibit aldehyde dehydrogenase causing elevated intracellular DOPAL levels (17,24). DOPAL is highly toxic and is hypothesized to be a causative factor in PD (15,22).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternatively, DA may undergo monoamine oxidase-catalyzed oxidative deamination to produce DOPAL, which can be further metabolized by aldehyde dehydrogenase to DOPAC (16,40). Previously, we showed that lipid peroxidation, which is closely associated with oxidative stress, can inhibit aldehyde dehydrogenase causing elevated intracellular DOPAL levels (17,24). DOPAL is highly toxic and is hypothesized to be a causative factor in PD (15,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, these mechanisms do not fully account for the high levels of toxicity associated with DOPAL. Therefore, we and others have hypothesized that DOPAL may be capable of undergoing oxidation to a quinone (16,17,20,22).…”
mentioning
confidence: 99%
See 3 more Smart Citations